Good morning, gorillas - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2002)
The magic tree house takes Jack and Annie to an African rainforest, where the siblings encounter gorillas and learn to communicate with them.
A stepping stone book.
Keywords: Gorilla -- Fiction; Human-animal communication -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction